Perceived privacy risks and trust dynamics: Rethinking mobile payment adoption in Indonesia - Rianmahardhika Sahid Budiharseno; Min-Joon Kim (Global Business & Finance Review (GBFR), 2023)
Purpose: This research aimed to explore and understand the intricacies of mobile payments within the Indonesian context, particularly focusing on the dynamic relationship between perceived privacy risks, trust, and the intention to adopt mobile payment services. Design/methodology/approach: The study employed a hybrid research methodology, integrating qualitative and quantitative analyses. Specifically, this research utilized Confirmatory Factor Analysis (CFA) model that evaluated the alignment of the proposed model with the observed data. The mobile payment privacy policies were analyzed through the identification of key textual features. Findings: The study revealed a revealed positive relationship between certain perceived risks (psychological and financial) and trust, suggesting that certain perceived risks might inadvertently foster trust. Conversely, time risk and performance risk negatively influence trust. This research also emphasized the pivotal role of trust in shaping user intentions toward mobile payments. Further findings highlighted the complex nature of privacy risks in the context of mobile payments and the significant surge in adoption rates during the COVID-19 pandemic. Research limitations/implications: This research was bound by a limited dataset size, which could influence the derived results. Potential inaccuracies from incomplete questionnaires might introduce non-statistical errors. With the ever-evolving nature of mobile payments, future studies could benefit from refining the research framework and incorporating additional variables. Originality/value: This study uniquely delves into the mobile payment scenario in Indonesia, challenging traditional views of risk and trust and offering fresh perspectives on consumer behavior. The innovative approach to analyzing mobile payment privacy policies and the spotlight on the role of perceived risks and trust in adoption intention set it apart. Its findings serve as a blueprint for both academics and practitioners in the mobile payment domain.
Keywords: 650; Mobile payments; Privacy risks; Trust; Adoption intention; Indonesia